Method for preparing three-dimensional grid magnesium aluminate composite intermediate layer for dissimilar material brazing through Joule thermal shock and application of three-dimensional grid magnesium aluminate composite intermediate layer
The three-dimensional grid magnesium aluminate composite intermediate layer was prepared by Joule thermal shock method, which solved the problem of uneven dispersion of the enhanced phase between the SiC space mirror and the Al/SiC composite material support, achieved uniform distribution and close combination of the enhanced phase, and improved the mechanical properties and preparation efficiency of the brazed joint.
Patent Information
- Application Number
- CN202510119057.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The brazing intermediate layer reinforcement phase between the existing SiC space mirror and the Al/SiC composite support is unevenly dispersed on the mesh structure, resulting in residual stress on the brazed joint and affecting the mechanical properties.
The three-dimensional mesh magnesium aluminate composite intermediate layer was prepared by Joule thermal shock method, and the MgAl2O4 precursor solution impregnation and carbon fiber cloth heating were achieved to achieve uniform distribution and close bonding of MgAl2O4 particles on the surface of the Nb mesh skeleton.
The structural performance and uniformity of the composite intermediate layer are significantly improved, and the particle agglomeration caused by long-term treatment in traditional heat treatment is avoided, the preparation cycle is shortened, and the mechanical properties and preparation efficiency are improved.
Smart Images

Figure CN119794491A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of brazing connection of space reflectors. Background Art
[0002] In order to cope with the increasingly complex and precise space observation and detection missions, the new generation of space reflectors uses lightweight SiC with excellent specific stiffness and thermal stability as the mirror material, and uses lightweight and high-strength Al / SiC composite materials with a SiC content of more than 40% as the annular support. At present, the SiC reflector and the Al / SiC composite support are still connected by traditional mechanical flanges, which not only significantly increases the overall weight of the optical system, but also easily deforms at the connection, thereby affecting the optical accuracy and thermal stability, making it difficult to meet the increasingly stringent space mission requirements. In comparison, brazing connection technology can effectively reduce the weight of the structure, provide good connection strength, reduce deformation, and help improve the accuracy and thermal stability of the optical system. Therefore, it is considered to be a more ideal alternative.
[0003] At present, there are few studies on the brazing connection of SiC and Al / SiC composites. Existing research mainly focuses on the brazing of each material with other materials. Al / SiC composites usually use Al-based brazing filler metals, while SiC brazing uses AgCu-based, Ni-based, Ti-based and other brazing fillers, which show good mechanical properties. Although the research is relatively limited, Al-based brazing filler metals show good compatibility and mechanical properties in the connection of SiC and Al / SiC composites, especially AlSiMg brazing filler metals. Due to the difference in thermal expansion coefficients between SiC and Al / SiC composites (SiC: 4.0×10 -6 / K, Al / SiC composite material: 12.0×10 -6 / K), brazed joints are prone to generate large residual stresses, especially in large-sized joints, this problem is more prominent, leading to cracks and decreased mechanical properties. Therefore, alleviating residual stress becomes a key problem. The particle reinforcement phase can relieve residual stress by regulating the thermal expansion coefficient, but there is currently no reinforcement phase suitable for Al-based solder. The grid structure of the porous metal skeleton-loaded reinforcement phase can evenly distribute the reinforcement phase, but the tight connection between the particle reinforcement phase and the grid skeleton is a key difficulty. If the particle reinforcement phase is separated from the grid skeleton during the brazing process, it will still cause local agglomeration of the reinforcement phase. Therefore, achieving a tight connection between the uniformly distributed reinforcement phase and the grid skeleton is a key link to ensure the effect of the composite intermediate layer on the gradient transition regulation of the thermal expansion coefficient of the joint. Summary of the invention
[0004] The present invention aims to solve the problem of uneven dispersion of the reinforcement phase of the existing brazing intermediate layer between a large-sized SiC space reflector and an Al / SiC composite material support on the grid structure, and further provide a method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock and its application.
[0005] A method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock is carried out in the following steps:
[0006] 1. Preparation of MgAl2O4 precursor solution:
[0007] dissolving magnesium nitrate and aluminum nitrate in deionized water to obtain a MgAl2O4 precursor solution;
[0008] 2. Impregnation:
[0009] The acid-washed porous Nb grid skeleton is immersed in a MgAl2O4 precursor solution, and finally dried to obtain an immersed grid skeleton;
[0010] 3. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer by Joule thermal shock:
[0011] The carbon fiber cloth, the soaked grid skeleton and the carbon fiber cloth are stacked in order, and the carbon fiber cloths on both sides are used as Joule heat sources. Under the conditions of vacuum, voltage of 15V to 30V and current of 30A to 90A, the heat is kept for 5s to 300s, and then the current is stopped to obtain a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials.
[0012] Application: It is used for brazing of SiC and Al / SiC composites.
[0013] The beneficial effects of the present invention are:
[0014] 1. The method of preparing a three-dimensional grid MgAl2O4 composite intermediate layer by Joule thermal shock proposed in the present invention realizes the uniform distribution and close bonding of the MgAl2O4 particle reinforcement phase on the surface of the Nb grid skeleton, avoiding the particle agglomeration phenomenon caused by high temperature and long-term treatment in the traditional heat treatment process. This uniform distribution significantly improves the structural performance and uniformity of the composite intermediate layer.
[0015] 2. The Joule thermal shock method significantly shortens the preparation cycle of the composite intermediate layer by rapidly heating up (1000-3000℃) and cooling down quickly in a short period of time. At the same time, it avoids the problems of high energy consumption and long process time in traditional heat treatment, greatly improving the preparation efficiency.
[0016] 3. Joule thermal shock technology not only avoids particle aggregation, but also can prepare nano-scale MgAl2O4 reinforcement phase particles, further improving the microstructure quality and mechanical properties of the composite intermediate layer, providing better performance support for the brazing joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the three-joule thermal shock temperature curve of step 1 of Example 1;
[0018] Figure 2 The morphology and element distribution diagram of the three-dimensional grid magnesium aluminate composite middle layer for brazing of dissimilar materials prepared in Example 1, (a) is the morphology, (b) is the distribution of Mg element in the middle of the composite, (c) is the distribution of Al element in the middle of the composite, and (d) is the distribution of O element in the middle of the composite;
[0019] Figure 3 This is a picture of the combination of the reinforcement phase and the matrix in the microstructure of the three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials prepared in Example 1;
[0020] Figure 4 The relationship curve between shear strength and strain of the three-dimensional grid magnesium aluminate composite intermediate layer assisted brazing joint prepared in Example 1 and the comparative experiment. DETAILED DESCRIPTION
[0021] Specific implementation method 1: This implementation method is a method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock, which is carried out in the following steps:
[0022] 1. Preparation of MgAl2O4 precursor solution:
[0023] dissolving magnesium nitrate and aluminum nitrate in deionized water to obtain a MgAl2O4 precursor solution;
[0024] 2. Impregnation:
[0025] The acid-washed porous Nb grid skeleton is immersed in a MgAl2O4 precursor solution, and finally dried to obtain an immersed grid skeleton;
[0026] 3. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer by Joule thermal shock:
[0027] The carbon fiber cloth, the soaked grid skeleton and the carbon fiber cloth are stacked in order, and the carbon fiber cloths on both sides are used as Joule heat sources. Under the conditions of vacuum, voltage of 15V to 30V and current of 30A to 90A, the heat is kept for 5s to 300s, and then the current is stopped to obtain a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials.
[0028] In this embodiment, MgAl2O4 (8.5×10 -6 / K) and Nb(7.5×10 -6 / K), using its gradient transition characteristics to relieve the residual stress of large-size joints and improve the mechanical properties of joints, thereby achieving high-quality brazing connections.
[0029] In step 2 of this specific implementation method, the soaked grid skeleton is naturally dried at room temperature, or treated by low-temperature drying (100° C.). This step ensures that the precursor solution completely penetrates and adheres to the surface of the Nb grid skeleton and its pores.
[0030] This specific embodiment uses carbon fiber cloth as a heating element, taking advantage of its high electrical conductivity and good thermal conductivity to ensure that the sample can be evenly heated during the Joule thermal shock process. The two ends of each piece of carbon fiber cloth are fixed to the heating electrodes of the Joule thermal shock device through appropriate clamps or contact terminals. Ensure that the carbon fiber cloth is in close contact with the electrode port to avoid uneven heat transfer caused by poor contact. Place the prepared impregnated sample between the two pieces of carbon fiber cloth to ensure that the sample is heated evenly.
[0031] This specific embodiment uses the Joule thermal shock method to heat up to 1000℃~3000℃ in a very short time, and quickly cools down after heating to achieve rapid quenching. This technology avoids the problem of reinforcing phase agglomeration that is easily caused by long-term high-temperature heat treatment, and achieves a close connection between the uniformly distributed reinforcing phase and the grid skeleton, which is very suitable for the preparation of high-melting-point oxides. The three-dimensional grid MgAl2O4 composite intermediate layer prepared by the Joule thermal shock method can not only achieve a close connection between the particle reinforcement phase and the matrix, but also effectively inhibit the aggregation and movement of the particle reinforcement phase, ensure the uniform dispersion of the particle reinforcement phase on the matrix, and at the same time, prepare a nano-level reinforcement phase, greatly improving the quality of the three-dimensional grid composite intermediate layer.
[0032] In this specific embodiment, during the Joule thermal shock process, the metal ions in the sample react to form magnesium aluminum spinel (MgAl2O4) particles, and deposit them on the surface of the porous Nb skeleton. After the heating is completed, the current is quickly stopped and the sample is rapidly cooled. Due to the characteristics of the Joule thermal shock method, the material can be cooled quickly within a short period of time after heating, avoiding excessive oxidation or physical property changes of the material at high temperature.
[0033] The beneficial effects of this embodiment are:
[0034] 1. The method for preparing a three-dimensional grid MgAl2O4 composite intermediate layer by Joule thermal shock proposed in this embodiment achieves uniform distribution and close bonding of the MgAl2O4 particle reinforcement phase on the surface of the Nb grid skeleton, avoiding the particle agglomeration phenomenon caused by high temperature and long-term treatment in the traditional heat treatment process. This uniform distribution significantly improves the structural performance and uniformity of the composite intermediate layer.
[0035] 2. The Joule thermal shock method significantly shortens the preparation cycle of the composite intermediate layer by rapidly heating up (1000-3000℃) and cooling down quickly in a short period of time. At the same time, it avoids the problems of high energy consumption and long process time in traditional heat treatment, greatly improving the preparation efficiency.
[0036] 3. Joule thermal shock technology not only avoids particle aggregation, but also can prepare nano-scale MgAl2O4 reinforcement phase particles, further improving the microstructure quality and mechanical properties of the composite intermediate layer, providing better performance support for the brazing joint.
[0037] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the concentration of magnesium nitrate in the MgAl2O4 precursor solution in step 1 is 0.01 mol / L to 0.5 mol / L. Other aspects are the same as those in specific embodiment 1.
[0038] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the molar ratio of magnesium nitrate to aluminum nitrate in step 1 is 1:2. The rest is the same as specific implementation method 1 or 2.
[0039] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that: the porous Nb mesh skeleton after pickling described in step 2 is specifically prepared according to the following steps: immersing the porous Nb mesh skeleton in a mixed solution containing hydrofluoric acid and nitric acid, treating for 1min to 10min, then rinsing with deionized water, and finally drying naturally or drying at low temperature to obtain the porous Nb mesh skeleton after pickling; the mixed solution containing hydrofluoric acid and nitric acid is specifically prepared by mixing hydrofluoric acid and nitric acid, the mass percentage of hydrofluoric acid is 10% to 30%; the mass percentage of nitric acid is 10% to 30%, and the volume ratio of hydrofluoric acid to nitric acid is 1: (3 to 5). The rest is the same as specific implementation method 3.
[0040] The pickling of this specific embodiment removes oxides and impurities on the surface of porous Nb, significantly enhancing the activity of the surface. The cleaned surface can better combine with the MgAl2O4 precursor, laying a foundation for the subsequent deposition and uniform distribution of particles, and reducing the formation of interface defects. The drying step after pickling ensures that there is no moisture and acid residue on the surface, avoiding the instability of the reaction during subsequent processing.
[0041] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the porosity of the porous Nb grid skeleton is 30% to 70%, and the average pore size of the grid is 50 μm to 300 μm. Other aspects are the same as specific embodiments 1 to 4.
[0042] In this specific embodiment, porous Nb is selected as the grid skeleton to ensure the uniform distribution of structural strength and reinforcement phase.
[0043] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: in step 2, the acid-washed porous Nb mesh skeleton is immersed in a MgAl2O4 precursor solution for 5 to 30 minutes. The rest is the same as specific embodiments 1 to 5.
[0044] In this specific embodiment, the porous Nb skeleton is fully impregnated to ensure that the precursor solution can completely penetrate the pores of the skeleton to achieve uniform deposition of the reinforcement phase particles. The mesh skeleton is taken out after immersion and gently shaken to remove excess precursor solution.
[0045] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the drying described in step 2 is carried out at room temperature to 100° C. for 1 to 3 hours. The rest is the same as specific embodiments 1 to 6.
[0046] In this embodiment, room temperature drying or low temperature drying ensures the solution to adhere firmly to the skeleton, while avoiding uneven particle distribution caused by premature decomposition of the precursor at high temperature.
[0047] Specific implementation eight: This implementation differs from specific implementations one to seven in that the thickness of the carbon fiber cloth in step three is 0.1 mm to 1 mm. The rest is the same as specific implementations one to seven.
[0048] Specific embodiment 9: This embodiment differs from any one of specific embodiments 1 to 8 in that: the vacuum described in step 3 is a vacuum degree of 10 -2 The vacuum environment is 10 Pa to 10 Pa. The rest is the same as the first to eighth embodiments.
[0049] In this specific implementation, the equipment is evacuated to effectively suppress excessive oxidation caused by high temperature during the Joule thermal shock process, and protect the microstructural integrity of the three-dimensional grid MgAl2O4 composite intermediate layer.
[0050] Specific embodiment ten: This embodiment is used for the application of a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials, and it is used for brazing of SiC and Al / SiC composite materials.
[0051] The following examples are used to verify the beneficial effects of the present invention:
[0052] Embodiment 1:
[0053] A method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock is carried out in the following steps:
[0054] 1. Preparation of MgAl2O4 precursor solution:
[0055] dissolving magnesium nitrate and aluminum nitrate in deionized water to obtain a MgAl2O4 precursor solution;
[0056] The concentration of magnesium nitrate in the MgAl2O4 precursor solution is 0.1 mol / L;
[0057] The molar ratio of magnesium nitrate to aluminum nitrate is 1:2;
[0058] 2. Impregnation:
[0059] The acid-washed porous Nb mesh skeleton was immersed in a MgAl2O4 precursor solution for 15 minutes, and finally dried at 100°C for 2 hours to obtain an immersed mesh skeleton;
[0060] The size of the porous Nb grid skeleton is 10 mm×10 mm×1 mm, the porosity is 60%, and the average pore size of the grid is 200 μm;
[0061] 3. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer by Joule thermal shock:
[0062] The carbon fiber cloth, soaked grid skeleton and carbon fiber cloth were stacked in this order. The carbon fiber cloth on both sides was used as the Joule heat source. -2 Under the conditions of 30V voltage and 60A current, the temperature was kept at 4000 ℃ for 10s, and then the current was stopped to obtain a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials.
[0063] The porous Nb mesh skeleton after pickling described in step 2 is specifically prepared according to the following steps: immersing the porous Nb mesh skeleton in a mixed solution containing hydrofluoric acid and nitric acid, treating for 5 minutes, then rinsing with deionized water, and finally drying for 2 hours at a temperature of 100°C to obtain a porous Nb mesh skeleton after pickling; the mixed solution containing hydrofluoric acid and nitric acid is specifically prepared by mixing hydrofluoric acid and nitric acid, the mass percentage of hydrofluoric acid is 10%; the mass percentage of nitric acid is 10%, and the volume ratio of hydrofluoric acid to nitric acid is 1:3.
[0064] The size of the carbon fiber cloth described in step 3 is 40 mm×10 mm×0.5 mm.
[0065] Comparative experiment:
[0066] MgAl2O4 particles are immersed in ethanol to form a MgAl2O4 suspension, a porous Nb grid skeleton is immersed in the MgAl2O4 suspension and ultrasonically dispersed, and excess solvent is removed by drying after immersion to obtain a three-dimensional grid magnesium aluminate composite intermediate layer.
[0067] Figure 1 This is the Joule thermal shock temperature curve of step three of Example 1; under the conditions of setting voltage 30V, current 60A, and insulation time 10s, the temperature rises rapidly from 0s to 2s, and quickly rises from room temperature (about 25°C) to above 1050°C. After 2s, the temperature stabilizes at around 1050°C and remains constant. After the 10s insulation time, the temperature drops rapidly, and the curve shows a trend of rapid cooling. This curve illustrates the characteristics of Joule thermal shock technology, namely rapid heating, precise temperature control, and rapid cooling.
[0068] Figure 2 The morphology and element distribution diagram of the three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials prepared in Example 1, (a) is the morphology, (b) is the distribution of Mg element in the middle of the composite, (c) is the distribution of Al element in the middle of the composite, and (d) is the distribution of O element in the middle of the composite. The cross nodes and pore structure of the three-dimensional grid can be seen. Here, the element point scanning ratio of the element Mg-Al-O is close to 1:2:4, and the molar ratio of the early precursor solution is limited to Mg:Al=1:2. At the same time, Mg-Al oxide preferentially generates MgAl2O4, which can prove the generation of MgAl2O4. It can be seen from the figure that the covering layer of the reinforcing phase particles (MgAl2O4) on the surface is tightly combined with the grid skeleton and evenly distributed on the surface of the pore structure. There is no obvious agglomeration phenomenon between the particles, indicating that the Joule thermal shock method effectively avoids the particle aggregation problem caused by long-term high temperature in traditional heat treatment.
[0069] Figure 3 This is a picture of the combination of the reinforcing phase and the matrix on the microstructure of the three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials prepared in Example 1. The morphology of the MgAl2O4 reinforcing phase particles can be clearly observed in the figure, which presents a polyhedral structure and a relatively regular particle shape, indicating that the crystal growth is stable during the Joule thermal shock process. The particle size of the reinforcing phase is about 100nm, which meets the characteristics of nano-scale reinforced materials. The interface between the reinforcing phase MgAl2O4 and the porous Nb skeleton is clear and flat, showing good bonding characteristics. There is no obvious stratification or gap at the interface, indicating that the Joule thermal shock method can achieve metallurgical bonding or chemical bonding between the reinforcing phase and the matrix in a short time, ensuring the overall strength and stability of the material. The figure shows that the reinforcing phase particles are evenly distributed, and there is no particle agglomeration or accumulation.
[0070] The three-dimensional grid magnesium aluminate composite intermediate layer prepared in Example 1 and the comparative experiment was used to braze SiC and Al / SiC composite materials:
[0071] The brazing material is AlSiMg, the welding temperature is 620℃, the holding time is 10min, and the size is 10mm×10mm×1mm. First, ensure that the surface of SiC and Al / SiC composite materials is clean and free of impurities, which can be cleaned with alcohol or acetone. The three-dimensional grid magnesium aluminate composite interlayer and AlSiMg brazing filler powder are placed in a vacuum container, and the three-dimensional grid magnesium aluminate composite interlayer is buried in the AlSiMg brazing filler powder, and then evacuated to a pressure of 0.1MPa. Under the condition of a pressure of 0.1MPa, it is maintained for 5min, and then the vacuum is released at a speed of 0.05MPa / min until the normal pressure is restored to obtain the composite interlayer filled with AlSiMg brazing filler. Then, the composite interlayer filled with AlSiMg brazing filler is placed between the SiC and Al / SiC composite surfaces to be welded to obtain the welded parts, and the welded parts are placed in a brazing furnace and evacuated for 10min until the vacuum degree is 5×10 -3 Pa, heat up to 620℃ and keep for 10min, the solder will fully flow at this temperature, fill the joint and form a firm connection.
[0072] Tested according to GB / T 11363-2008 standard; Figure 4 The relationship curve between the shear strength and strain of the three-dimensional grid magnesium aluminate composite intermediate layer assisted brazing joint prepared in Example 1 and the comparative experiment; it can be seen from the figure that the composite intermediate layer prepared by the Joule thermal shock method has higher shear strength and ductility. The shear strength peak is close to 120MPa, which is significantly higher than the approximately 85MPa prepared by the original method. The material prepared by Joule thermal shock only reaches fracture when the strain is close to 40%, while the material prepared by the original method fractures at about 20%. The Joule thermal shock preparation method significantly improves the shear strength and ductility of the composite intermediate layer assisted brazing joint, exhibits more superior mechanical properties, and is suitable for the preparation needs of high-performance materials.
Claims
1. A method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock, characterized in that It is carried out in the following steps:
1. Preparation of MgAl2O4 precursor solution: dissolving magnesium nitrate and aluminum nitrate in deionized water to obtain a MgAl2O4 precursor solution; 2. Impregnation: The acid-washed porous Nb grid skeleton is immersed in a MgAl2O4 precursor solution, and finally dried to obtain an immersed grid skeleton; 3. Preparation of three-dimensional grid MgAl2O4 composite intermediate layer by Joule thermal shock: The carbon fiber cloth, the soaked grid skeleton and the carbon fiber cloth are stacked in order, and the carbon fiber cloths on both sides are used as Joule heat sources. Under the conditions of vacuum, voltage of 15V to 30V and current of 30A to 90A, the heat is kept for 5s to 300s, and then the current is stopped to obtain a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials.
2. The method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 1, characterized in that The concentration of magnesium nitrate in the MgAl2O4 precursor solution described in step 1 is 0.01 mol / L to 0.5 mol / L.
3. The method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 1, characterized in that The molar ratio of magnesium nitrate to aluminum nitrate described in step 1 is 1:
2.
4. The method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 1, characterized in that The porous Nb mesh skeleton after pickling described in step 2 is specifically prepared according to the following steps: immersing the porous Nb mesh skeleton in a mixed solution containing hydrofluoric acid and nitric acid, treating for 1min to 10min, then rinsing with deionized water, and finally drying naturally or drying at low temperature to obtain the porous Nb mesh skeleton after pickling; the mixed solution containing hydrofluoric acid and nitric acid is specifically prepared by mixing hydrofluoric acid and nitric acid, the mass percentage of hydrofluoric acid is 10% to 30%; the mass percentage of nitric acid is 10% to 30%, and the volume ratio of hydrofluoric acid to nitric acid is 1: (3 to 5).
5. The method for preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 4, characterized in that The porosity of the porous Nb grid skeleton is 30% to 70%, and the average pore size of the grid is 50 μm to 300 μm.
6. The method of preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 1, characterized in that In step 2, the pickled porous Nb grid skeleton is immersed in a MgAl2O4 precursor solution for 5 to 30 minutes.
7. The method of preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 1, characterized in that The drying in step 2 is specifically drying at room temperature to 100° C. for 1 h to 3 h.
8. The method of preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 1, characterized in that The thickness of the carbon fiber cloth described in step 3 is 0.1 mm to 1 mm.
9. The method of preparing a three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials by Joule thermal shock according to claim 1, characterized in that The vacuum in step 3 is 10 -2 Vacuum environment of Pa~10Pa.
10. Application of the three-dimensional grid magnesium aluminate composite intermediate layer for brazing of dissimilar materials prepared as claimed in claim 1, characterized in that It is used for brazing of SiC and Al / SiC composite materials.
Citation Information
Patent Citations
Preparation method of free-agglomeration MgAl2O4 nanometer particle powder
CN103265278A
Method for assisting brazing of dissimilar materials through three-dimensional negative expansion network composite intermediate layer material
CN113231706A
Self-disinfection biological protection nano textile, preparation method thereof and remote real-time human motion detection system
CN118617843A
METHOD FOR JOINING, ASSEMBLING PARTS MADE OF SiC-BASED MATERIALS BY NON-REACTIVE BRAZING, BRAZING COMPOSITIONS, AND JOINT AND ASSEMBLY OBTAINED BY SAID METHOD
US20130004235A1
Lithium battery positive electrode material precursor and its preparation method and application
US20240239689A1